A study on the Necessity and Feasibility of Sports Clubs at Hubei Enshi College College - ding, yiyi (Pacific International Journal, 2023)
In recent years, the Chinese government has issued a series of documents, including the National Guideline for Teaching Physical Education Courses in Ordinary Higher Education Schools, the Basic Standards for Physical Education Work in Higher Education Schools, and the Opinions of the General Office of the State Council on Strengthening School Physical Education for the Overall Development of Students’ Physical and Mental Health. In response to these documents, colleges and universities in China have been actively promoting sports reform initiatives. This study uses literature review, Delphi method, and mathematical statistics to investigate the current situation of sports development on the campus of Hubei Enshi College, and to analyze the necessity and feasibility of sports clubbased teaching. Specifically, the study focuses on the development of sports clubs at Hubei Enshi College, and examines the challenges and opportunities for reform. The study finds that the development of sports clubs at Hubei Enshi College lacks an efficient and complete organizational and management framework, and that the current teaching situation faces the dilemma of "one size fits all". In addition, the study identifies the lack of integration of teaching resources between the first and second classes, and the lack of branding effect of campus sports culture. The study concludes by providing feasible suggestions for the optimal development of sports clubs at Hubei Enshi College, in line with the university’s educational philosophy of "establishing moral education, teaching students according to their abilities, and applying learning to practice".